Transdiagnostic Mechanisms of Mental Health During the COVID-19 Pandemic on Adults and Families in Germany: Study Protocol of a Cross-Sectional and 1-Year Longitudinal Study - Volkert, Jana; Taubner, Svenja; Berning, Anna; Kling, Laura; Wießner, Hannah; Georg, Anna K.; Holl, Julia (Frontiers in Psychology, 2021)
Background: Since the outbreak of COVID-19 pandemic, psychological distress is increased. Transdiagnostic mechanisms, including trauma, personality functioning, mentalizing and emotion regulation are considered relevant to the development and maintenance of mental health problems and therefore may play a role in individuals’ reactions to the pandemic. Aim: To identify moderating and mediating factors associated with pandemic-related distress and mental health problems in adults and families, we aim to investigate the interactions of interpersonal trauma (childhood trauma and domestic violence), psychological capacities (personality functioning, mentalizing and emotion regulation) and pandemic-related adversity on psychological distress during the COVID-19 pandemic. Furthermore, we aim to investigate behavioral and cognitive consequences of the pandemic (e.g., media consumption, vaccination status, conspiracy beliefs). Methods: Using an online-based cross-sectional and longitudinal design, we will investigate a sample of adult participants recruited via online platforms in German-speaking countries over the course of one year with four measurements points via self-report instruments (personality functioning: PID5BF+; mentalizing: MentS, PRFQ; emotion regulation: DERS-SF; mental health problems: PHQ-9, GAD-7; a composite pandemic-related stress score). Structural equation and multi-level modeling will be performed for data analyses. Implications: This study will provide data on the moderating and mediating effects of trauma, personality functioning and mentalizing during the pandemic in a large community sample, particularly on vulnerable groups like families. Identifying transdiagnostic mechanisms of psychopathology in the course of a pandemic crisis may provide valuable insight for the development of pre- and intervention measures for potential psychological distress during and post the pandemic.